Phenotypic and genotypic characterization of Colombian clinical isolates of Sporothrix spp (2023)
ABSTRACT: Introduction: For over a century, Sporothrix schenckii was considered the sole species responsible for sporotrichosis. In 2007, scientific community confirmed the disease could be caused by various Sporothrix species. These species differed in their virulence factors and their antifungal sensitivity. Objective: This study aims to characterize 42 Colombian clinical isolates of Sporothrix spp. phenotypically and genotypically. Material and methods: Forty-two clinical isolates were characterized using phenotypic methods. It involved various culture media to determine their growth range at different temperatures and to assess the type and distribution of pigment and colony texture. Microscopic morphology was evaluated through microcultures, as well as the conidia diameter, type of sporulation, and morphology. Additionally, the assimilation of carbohydrates was selected as a physiological trait for species identification. Genotyping of 40 isolates was performed through partial amplification of the calmodulin gene, followed by sequence analysis. Results: Molecular studies enabled the identification of 32 isolates of S. schenckii and 8 isolates of S. globosa. The combination of phenotypic and genotypic methods eased these species characterizations and the recognition keys development based on parameters such as growth diameter at 25 and 30 ºC, colony texture (membranous or velvety) on potato dextrose agar, and microscopic morphology with predominance of pigmented triangular, elongated oval globose, or subglobose conidia. Conclusions: Confirmation of the phenotypic characteristics and molecular analysis is crucial for identifying Sporothrix species and determining adequate treatment. This study represents the first phenotypical and genotypical characterization of clinical isolates of Sporothrix spp. reported in Colombia.